Development of high intensity CDC combustor for gas turbine engines - Arghode, Vaibhav K.; Gupta, Ashwani K. (Applied energy, 2011)
Colorless distributed combustion (CDC) has been demonstrated to provide ultra-low emission of NO x and CO, improved pattern factor and reduced combustion noise in high intensity gas turbine combustors. The key feature to achieve CDC is the controlled flow distribution, reduce ignition delay, and high speed injection of air and fuel jets and their controlled mixing to promote distributed reaction zone in the entire combustion volume without any flame stabilizer. Large gas recirculation and high turbulent mixing rates are desirable to achieve distributed reactions thus avoiding hot spot zones in the flame. The high temperature air combustion (HiTAC) technology has been successfully demonstrated in industrial furnaces which inherently possess low heat release intensity. However, gas turbine combustors operate at high heat release intensity and this result in many challenges for combustor design, which include lower residence time, high flow velocity and difficulty to contain the flame within a given volume. The focus here is on colorless distributed combustion for stationary gas turbine applications. In the first part of investigation effect of fuel injection diameter and air injection diameter is investigated in detail to elucidate the effect fuel/air mixing and gas recirculation on characteristics of CDC at relatively lower heat release intensity of 5 MW/m 3 atm. Based on favorable conditions at lower heat release intensity the effect of confinement size (reduction in combustor volume at same heat load) is investigated to examine heat release intensity up to 40 MW/m 3 atm. Three confinement sizes with same length and different diameters resulting in heat release intensity of 20 MW/m 3 atm, 30 MW/m 3 atm and 40 MW/m 3 atm have been investigated. Both non-premixed and premixed modes were examined for the range of heat release intensities. The heat load for the combustor was 25 kW with methane fuel. The air and fuel injection temperature was at normal 300 K. The combustor was operated at 1 atm pressure. The results were evaluated for flow field, fuel/air mixing and gas recirculation from numerical simulations and global flame images, and emissions of NO, CO from experiments. It was observed that the larger air injection diameter resulted in significantly higher levels of NO and CO whereas increase in fuel injection diameter had minimal effect on the NO and resulted in small increase of CO emissions. Increase in heat release intensity had minimal effect on NO emissions, however it resulted in significantly higher CO emissions. The premixed combustion mode resulted in ultra-low NO levels (<1 ppm) and NO emission as low as 5 ppm was obtained with the non-premixed flame mode.